Embracing Diversity in Education: Fostering Inclusive Learning Environment in SDIT Ibnu Taimiyah as a School Based on Noble Character - Masrifdah, Siti; Najmy Al Hakimy, Moch (UIN Sunan Gunung Djati Bandung, 2025)
Education and diversity are two objects that cannot be separated. Since students have varied backgrounds, it must be able to accommodate the diversity of their characters, potentials, and abilities which is called an inclusive program. One of the schools in Bandung that has implemented this program is SDIT Ibnu Taimiyah. It is a school based on the development of noble character. This research uses qualitative methods to investigate how the foundation's chairperson and principal encourage the teachers to implement an inclusive learning environment in school. The interview and observation revealed that the foundation's chairperson can handle inclusive students and is actively involved in supporting them. Additionally, the principal ensures that teachers receive training on how to treat inclusive students. As an outcome, the teachers can embody a diverse school environment and prevent inclusive student bullying.